Fabrication and tribological performance of a laser-textured hardmetal guiding stone for honing processes. (November 2019) - Fang, Shiqi; Klein, Sven; Hsu, Chia-Jui; Llanes, Luis; Gachot, Carsten; Bähre, Dirk
Abstract: Honing is often implemented as surface finish process by improving geometrical and form precision of workpieces. Guiding stones, usually made of hard materials with requirement of excellent tribological properties, play a key role as a supporting part in the honing tool. In this paper, cemented carbides are intended for guiding application as substitute of diamond or CBN composites. Innovative surface textures, namely crossing-line patterns and dimple arrays, are fabricated by means of short pulse laser on a cemented tungsten carbide (hardmetal) grade. Implementation of these processing conditions yields satisfactory geometrical accuracy. The cemented carbide stones patterned by laser together with a traditional diamond guiding stone were tested on a lubricated pin-on-disc tribometer. Both cross-line patterns or dimple arrays are found to improve frictional conditions compared to the traditional guiding stone, but the former are more favorable to build up a stable sliding scenario with minimized friction than the latter. Pattern density has a more significant impact on friction, diminishing in the case of dimple arrays. Highlights: Reproduction of honed surface topography on cemented carbide grade Satisfactory surface integrity and geometrical precision obtained by nanosecond laser. Crossing-line patterns achieved better frictional conditions than dimple arrays. Pattern density has a significant impact on frictional performance.